Creation of a system for designing textile patterns using an iterative function system - Zhang, Chunxia (International Journal of Innovative Research and Scientific Studies, 2024)
This study conducted research to tackle the issues of inadequate pattern design impacts and pattern distortion in textile pattern design systems. Using the experimental verification method, the iterative function system is tried to be used in the textile pattern design system. Through the iterative function system, the system hardware structure configuration can be improved, the system software function can be optimized, the system operation efficiency can be improved, and the pattern design and textile clarity and accuracy can be guaranteed. The textile pattern design system based on an iterated function system has high practicability in the practical application process, which can better prove the system’s efficiency and improve the accuracy of pattern simulation. The fractal pattern created based on fractal theory perfectly combines science and art. These patterns can greatly enrich the pattern types of textiles and shorten the pattern design cycle. At the same time, it also breaks the habitual thinking of the human brain to a certain extent, broadens the thinking and vision for designers, helps designers develop new creative resources, and takes it as the entry point of pattern design in the textile industry, bringing new vitality to textile art design. This paper provides rich experience and guidance for textile pattern design systems based on iterated function systems and enriches the existing literature.